1995
DOI: 10.1111/j.1749-7345.1995.tb00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Masculinization of Channel Catfish Ictalurus punctatus by Oral Administration of Trenbolone Acetate

Abstract: All‐male populations of channel catfish, Ictalurus punelatus, were produced by feeding a diet containing trenbolone acetate to swim‐up fry for 60 d. This hormone was effective in producing 100% males at doses of 50 to 150 mg/kg of diet. Fish that received 0 or 1 mg/kg of diet did not differ from the expected 1:1 sex ratio. Survival of control fish and fish fed diets containing trenbolone acetate were similar (P > 0.05) at the end of the treatment period and after a 60‐d grow‐out period. Our results represent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…Specific in vivo responses vary, but include several typical of exposure to anabolic androgens including growth enhancement, masculinization of females, and alterations in accessory sex organs in males. In further studies with the channel catfish, Davis et al [22] found that the trenbolone acetate treatment regime used in their earlier study [21] did not produce functional males, in that the treated fish had decreased plasma testosterone concentrations at maturity and were infertile. Galvez et al [21], Davis et al [22], and Galvez and Morrison [35] assessed the effects of trenbolone acetate on channel catfish and tilapia from an aquacultural perspective.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Specific in vivo responses vary, but include several typical of exposure to anabolic androgens including growth enhancement, masculinization of females, and alterations in accessory sex organs in males. In further studies with the channel catfish, Davis et al [22] found that the trenbolone acetate treatment regime used in their earlier study [21] did not produce functional males, in that the treated fish had decreased plasma testosterone concentrations at maturity and were infertile. Galvez et al [21], Davis et al [22], and Galvez and Morrison [35] assessed the effects of trenbolone acetate on channel catfish and tilapia from an aquacultural perspective.…”
Section: Discussionmentioning
confidence: 94%
“…In mammals, 17-␤-trenbolone activates androgen-dependent gene expression in vitro with a potency equivalent to or greater than dihydroxytestosterone, a potent natural androgen [14,16,34]. Galvez et al [21], Davis et al [22], and Galvez and Morrison [35] assessed the effects of trenbolone acetate on channel catfish and tilapia from an aquacultural perspective. inchem.org/documents/jecfa/jecmono/v25je08.htm672)].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was previously believed that androgens administered via the diet during early stages of morphological sex determination were aromatized within catfish, thus resulting in a female skewed population (Goudie et al 1983). However, it is currently not believed that aromatase is responsible, based on studies indicating that the use of nonaromatizable dihydrotestosterone (DHT) results in the feminization of channel catfish, even in the presence of the estrogen inhibitor clomiphene cirate, while trenbolone acetate (also a nonaromatizable androgen) produces phenotypic males (Davis et al 1992;Galvez et al 1995). Within mammals, DHT serves to regulate brain aromatase; however, within goldfish, DHT does not alter aromatase activity (Pasmanik et al 1988;Forlano and Bass 2005).…”
Section: Discussionmentioning
confidence: 99%